Crosslinking and mechanical properties significantly influence cell attachment, proliferation, and migration within collagen glycosaminoglycan scaffolds. - O'BRIEN, FERGAL (My University, 2011)
Crosslinking and the resultant changes in mechanical properties have been shown to influence cellular activity within collagen biomaterials. With this in mind, we sought to determine the effects of crosslinking on both the compressive modulus of collagen-glycosaminoglycan scaffolds and the activity of osteoblasts seeded within them. Dehydrothermal, 1-ethyl-3-3-dimethyl aminopropyl carbodiimide and glutaraldehyde crosslinking treatments were first investigated for their effect on the compressive modulus of the scaffolds. After this, the most promising treatments were used to study the effects of crosslinking on cellular attachment, proliferation, and infiltration. Our experiments have demonstrated that a wide range of scaffold compressive moduli can be attained by varying the parameters of the crosslinking treatments. 1-Ethyl-3-3-dimethyl aminopropyl carbodiimide and glutaraldehyde treatments produced the stiffest scaffolds (fourfold increase when compared to dehydrothermal crosslinking). When cells were seeded onto the scaffolds, the stiffest scaffolds also showed increased cell number and enhanced cellular distribution when compared to the other groups. Taken together, these results indicate that crosslinking can be used to produce collagen-glycosaminoglycan scaffolds with a range of compressive moduli, and that increased stiffness enhances cellular activity within the scaffolds.
PUBLISHED
Keywords: Bioengineering; DERMAL SHEEP COLLAGEN; Next Generation Medical Devices